Anesthetic management of hip fracture in geriatric patient with respiratory and heart failure using pericapsular nerve group block - Zejun Niu, MD; Xiaolin Xu, Bachelor; Haichen Chu, MD; Jihui Yin, Master (Medicine, 2022)
Abstract. Introduction:. Hip fracture with severe cardiopulmonary and cerebral dysfunction is a relatively common problem in the elderly population and poses a great challenge to anesthetic management. Pericapsular nerve group (PENG) block combined with nerve blocks of the hip region has recently attracted significant interest from anesthesiologists, and very few reports on its anesthetic management exist. Patient concerns:. Patient suffered from the right femoral neck fracture, combined with respiratory failure, heart failure, moderate-to-severe pulmonary hypertension, cerebral infarction, atrial fibrillation, and cognitive dysfunction. Diagnosis:. Because of right femoral neck fracture, artificial femoral head replacement was scheduled for this patient. Interventions:. Ultrasound-guided PENG block combined with sacral plexus, thoracic 11 to 12 paravertebral block, and lateral femoral cutaneous block were performed to a high-risk elderly patient. Outcomes:. The patient successfully received artificial femoral head replacement with our effective anesthesia techniques and no postoperative complication was reported. Conclusions:. Among elderly patients with multiple organ dysfunction undergoing hip surgery, PENG block combined with nerve blocks of the hip region is an ideal anesthesia method. This case demonstrated that these regional analgesia techniques had a stable hemodynamic process, satisfactory anesthetic effect, effective postoperative analgesia, and no effect on postoperative cognitive function. Further studies are needed to determine the appropriate doses of local anesthetics in the elderly with multiple organ system failure to reduce delayed local anesthesia systemic toxicity.